Development of a New Radiofluorinated Quinoline Analog for PET Imaging of Phosphodiesterase 5 (PDE5) in Brain - Jianrong Liu; Barbara Wenzel; Sladjana Dukic-Stefanovic; Rodrigo Teodoro; Friedrich-Alexander Ludwig; Winnie Deuther-Conrad; Susann Schröder; Jean-Michel Chezal; Emmanuel Moreau; Peter Brust; Aurélie Maisonial-Besset (MDPI AG, 2016)
Phosphodiesterases (PDEs) are enzymes that play a major role in cell signalling by hydrolysing the secondary messengers cyclic adenosine monophosphate (cAMP) and/or cyclic guanosine monophosphate (cGMP) throughout the body and brain. Altered cyclic nucleotide-mediated signalling has been associated with a wide array of disorders, including neurodegenerative disorders. Recently, PDE5 has been shown to be involved in neurodegenerative disorders such as Alzheimer's disease, but its precise role has not been elucidated yet. To visualize and quantify the expression of this enzyme in brain, we developed a radiotracer for specific PET imaging of PDE5. A quinoline-based lead compound has been structurally modified resulting in the fluoroethoxymethyl derivative ICF24027 with high inhibitory activity towards PDE5 (IC50 = 1.86 nM). Radiolabelling with fluorine-18 was performed by a one-step nucleophilic substitution reaction using a tosylate precursor (RCY(EOB) = 12.9% ± 1.8%; RCP > 99%; SA(EOS) = 70-126 GBq/μmol). In vitro autoradiographic studies of [18F]ICF24027 on different mouse tissue as well as on porcine brain slices demonstrated a moderate specific binding to PDE5. In vivo studies in mice revealed that [18F]ICF24027 was metabolized under formation of brain penetrable radiometabolites making the radiotracer unsuitable for PET imaging of PDE5 in brain.